ญาณวิทยาตามทัศนะของพุทธปรัชญาเถรวาท - บงกชกาญจน์, นาวาเอกนพดล (วารสาร ศึกษาศาสตร์ มมร; Vol 6 No 1 (2018): วารสารศึกษาศาสตร์ มมร ปีที่ 6 ฉบับที่ 1 (มกราคม - มิถุนายน 2561), 2018)
บทคัดย่อ              บทความวิชาการนี้ ผู้เขียนต้องการค้นหาคำตอบที่เกี่ยวกับญาณวิทยาตามทัศนะของ     พุทธปรัชญาเถรวาท โดยใช้กรอบแนวคิดของญาณวิทยา ซึ่งศึกษาเกี่ยวกับความรู้ของมนุษย์หรือวิธี การแสวงหาความรู้ของมนุษย์ และเชื่อว่าความรู้เป็นสิ่งที่มีอยู่จริง และเราสามารถแสวงหาความรู้นั้นได้         ผลจากการศึกษา พบว่า พุทธปรัชญาเถรวาทถือว่าความรู้ (ปัญญา) เป็นกุญแจสำคัญที่จะนำไปสู่เป้าหมายสูงสุดของชีวิตด้วยการรู้แจ้งตามหลักธรรมคำสอนของพระพุทธเจ้า จุดเริ่มต้นของความรู้ก็เริ่มต้นมาจากการตรัสรู้ของพระพุทธเจ้านั้นเอง ส่วนความหมายของความรู้นั้นจะมีลักษณะรู้และเข้าใจตามความเป็นจริง ตามสภาวธรรมที่เกิดขึ้นและความรู้ที่เกิดขึ้นนั้นจะต้องมาจากการปฏิบัติธรรมทางจิตใจที่เกิดขึ้นจากภายในโดยผ่านการฝึกฝนอบรมจิตจนมีจิตไม่หวั่นไหวต่อสิ่งใด และเข้าใจตามสภาวธรรมตามความเป็นจริงของอริยสัจ ตามทัศนะของพุทธปรัชญาความรู้เกิดจากสุตมยปัญญา เป็นความรู้ที่เกิดจากการศึกษาอบรม เล่าเรียน การได้ฟัง หรือการอ่าน จินตามยปัญญา เป็นความรู้ที่เกิดจากการคิดใคร่ครวญอย่างมีระบบ พิจารณาอย่างรอบคอบอยู่ในหลักการของเหตุ ซึ่งทั้งสองนี้เป็นปัญญาทำให้มีความรู้ที่เป็นจริงได้ในระดับสมมติสัจจะ และภาวนามยปัญญา เป็นความรู้ที่ได้รับจากการฝึกฝนอบรมจิตลงมือปฏิบัติอย่างถูกต้องจนเกิดความรู้แจ้ง เปรียบเทียบได้กับ ประจักษ์ประมาณ ทำให้มีความรู้ระดับปรมัตถ์ได้ และระดับความรู้แบ่งเป็น ๒ ระดับ คือ ๑) ความรู้ระดับสามัญ เป็นความรู้ที่ชาวโลกสมมติกันขึ้นมาเป็นความรู้ที่ถ่ายทอดจากผู้อื่นสืบต่อกันมาอันเป็นการรู้สมมติสัจจะ และ ๒) ความรู้ระดับสูงเป็นความรู้ที่แท้จริงที่อยู่พ้นจากประสาทสัมผัสธรรมดา อันเป็นการรู้ปรมัตถสัจจะทำให้เข้าใจสภาพความจริงสามารถพ้นจากทุกข์ถึงเป้าหมายที่แท้จริงได้   Abstract              This article, the author needs to find answers about the epistemology of the Theravada Buddhist philosophy. Using the concept of epistemology which study about the human knowledge or how to seek knowledge of human and believe that knowledge is real and we can seek that knowledge. The results of the study found that the Theravada Buddhist philosophy holds that knowledge is the key to the ultimate goal of life through enlightenment based on the doctrine of the Buddha. The beginning of knowledge begins with the enlightenment of the Buddha himself. The meaning of knowledge is the nature of knowledge and understanding. The moral of the Dharma and the knowledge that must come from the mental internally arising from the practice of mental training to the mind does not affect anything and to understand the truth of the Dharma.              According to the Buddhist philosophy, knowledge is born of intelligence. It is the knowledge that is born of education, training, listening, or reading. The wisdom of knowledge is the result of systematic thinking, carefully considered in the principle of cause. Both of these are intellectuals, enabling them to have conventional truth. And wisdom prayer is the knowledge gained from the practice of mental training to practice correctly until enlightenment comparing with the apparently making to have the ultimate knowledge. And the level of knowledge is divided into two levels: 1) Worldly knowledge is the knowledge that the world is assuming that knowledge is conveyed by others, which is conventional truth and 2) Ultimate knowledge is the true knowledge beyond the ordinary sense. This is a knowledge of truth. Understand the reality of being away from ordinary senses. The ultimate truth make to understand the reality and can be out of suffering and reach to real goal.